2016
DOI: 10.1007/s00395-016-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Mild endothelial dysfunction in Sirt3 knockout mice fed a high-cholesterol diet: protective role of a novel C/EBP-β-dependent feedback regulation of SOD2

Abstract: Sirtuin 3 (Sirt3) is an NAD+-dependent mitochondrial deacetylase associated with superoxide dismutase 2 (SOD2)-mediated protection from oxidative stress. We have reported accelerated weight gain and impaired metabolic flexibility in atherosclerotic Sirt3−/− mice. Oxidative stress is a hallmark of endothelial dysfunction. Yet, the role of Sirt3 in this context remains unknown. Thus, we aimed to unravel the effects of endogenous Sirt3 on endothelial function and oxidative stress. Knockdown of Sirt3 in human aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Previous studies have revealed close relation among SIRT3, oxidative stress and endothelial function [ 28 , 30 ]. Furthermore, SOD2, an important substrate of SIRT3, has powerful activity to suppress ROS production.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have revealed close relation among SIRT3, oxidative stress and endothelial function [ 28 , 30 ]. Furthermore, SOD2, an important substrate of SIRT3, has powerful activity to suppress ROS production.…”
Section: Resultsmentioning
confidence: 97%
“…SIRT3 protects against exaggerated oxidative stress by directly deacetylating and activating Mn-SOD. However, SIRT3 deficiency only mildly impairs endothelium-dependent relaxation under challenge with an atherogenic diet (Winnik, et al, 2016). Also, in a diet-induced atherosclerosis model in LDLr −/− mice, SIRT3 deficiency does not affect lesion formation, nor plaque instability, despite hepatic protein hyperacetylation in the mitochondria and elevated circulating level of malondialdehyde (an index of lipid peroxidation) (Winnik, et al, 2014).…”
Section: F Sirt2mentioning
confidence: 99%
“…SIRT3 can also manage NAD+ levels to regulate mitochondrial function, offering protection against liver injury associated with fatty liver (Kendrick et al ., ) and/or acute kidney injury (Morigi et al ., ). Because SIRT3 KO mice cannot maintain SOD2 homoeostasis and ROS level, they suffer from mild endothelial dysfunction when fed with high cholesterol diet (Winnik et al ., ).…”
Section: Introductionmentioning
confidence: 97%